Potential Vitamin E Signaling Mediators in Skeletal Muscle - Elisabetta Meacci; Antony Chirco; Mercedes Garcia-Gil (MDPI AG, 2024)
Vitamin E (Vit E) deficiency studies underline the relevance of this vitamin in skeletal muscle (SkM) homeostasis. The knowledge of the effectors and modulators of Vit E action in SkM cells is limited, especially in aging and chronic diseases characterized by a decline in musculoskeletal health. Vit E comprises eight fat-soluble compounds grouped into tocopherols and tocotrienols, which share the basic chemical structure but show different biological properties and potentials to prevent diseases. Vit E has antioxidant and non-antioxidant activities and both favorable and adverse effects depending on the specific conditions and tissues. In this review, we focus on the actual knowledge of Vit E forms in SkM functions and new potential signaling effectors (i.e., bioactive sphingolipids and myokines). The possible advantages of Vit E supplementation in counteracting SkM dysfunctions in sarcopenia and under microgravity will also be discussed.